2014
DOI: 10.1001/jamasurg.2013.3049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Breast Conservation Therapy vs Mastectomy on Disease-Specific Survival for Early-Stage Breast Cancer

Abstract: Patients who underwent BCT have a higher breast cancer-specific survival rate compared with those treated with mastectomy alone or mastectomy with radiation for early-stage invasive ductal carcinoma. Further investigation is warranted to understand what may be contributing to this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
260
2
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 326 publications
(293 citation statements)
references
References 14 publications
22
260
2
9
Order By: Relevance
“…There is now recent data to suggest that BCT may confer a higher breast cancer-specific survival rate compared with mastectomy (Agarwal et al, 2014). Although the reasons behind this observation have yet to be clearly elucidated, this new information elevates the role of BCT in women with early breast cancer.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…There is now recent data to suggest that BCT may confer a higher breast cancer-specific survival rate compared with mastectomy (Agarwal et al, 2014). Although the reasons behind this observation have yet to be clearly elucidated, this new information elevates the role of BCT in women with early breast cancer.…”
Section: Discussionmentioning
confidence: 95%
“…This study was undertaken to evaluate the validity of this syllogism, and if utilisation of BCT in Asian women can be improved. If possible, higher rates of breast conservation could lead to better survival outcomes in Asian women (Agarwal et al, 2014).…”
Section: Evaluation Of Eligibility and Utilization Of Breast Conservamentioning
confidence: 99%
See 2 more Smart Citations
“…Ogawa et al [9] emphasized that BCT has become the standard strategy for breast cancer surgery ensuring local control with acceptable cosmetic results. Agarwal et al [10] reported that patients who underwent BCT had a higher breast cancer-specific survival rate compared with those treated with mastectomy for early-stage invasive ductal carcinoma.…”
Section: Introductionmentioning
confidence: 99%